OCULAR PERFUSION CHARACTERIZATION OF LASER SPECKLE IMAGES FOR RABBIT MODEL OF EXTERNAL CAROTID ARTERY OCCLUSION - BHATTI, MEHWISH SABA (2018)
Animal models are indispensable for translational research. Animal models of carotid artery disease under deep anesthesia have not been characterized using laser speckle flowgraphy. This study aims to establish the effect of occlusion of internal carotid (ICA) and external carotid artery (ECA) on ocular blood supply of rabbits. In addition, the effects of reperfusion of these two vessels are studied